Clinical Characteristics and Prognostic Factors in Pediatric Vascular Tumors - Rujkijyanont P; Traivaree C; Satayasoontorn K; Photia A; Lertvivatpong N; Monsereenusorn C (Dove Medical Press, 2021)
Piya Rujkijyanont,1 Chanchai Traivaree,1 Kantang Satayasoontorn,2 Apichat Photia,1 Nawachai Lertvivatpong,1 Chalinee Monsereenusorn1 1Division of Hematology/Oncology, Department of Pediatrics, Phramongkutklao Hospital and Phramongkutklao College of Medicine, Bangkok, Thailand; 2Department of Pathology, Phramongkutklao Hospital and Phramongkutklao College of Medicine, Bangkok, ThailandCorrespondence: Chalinee MonsereenusornDivision of Hematology/Oncology, Department of Pediatrics, Phramongkutklao Hospital and Phramongkutklao College of Medicine, 315 Ratchawithi Road Ratchathewi, Bangkok, 10400, ThailandEmail chalinee_monsereenusorn@pedpmk.orgBackground: The most common type of vascular tumors reported among children is hemangioma. The determinant factors to predict clinical outcomes among those patients were not well studied.Objective: The study aimed to explore clinical characteristics and treatment approaches as well as associated prognostic factors of vascular tumors specifically in a pediatric population.Methods: Pediatric patients with a confirmed diagnosis of vascular tumors between January 1, 2005 and December 31, 2017 were enrolled in this study. Clinical data includes initial clinical manifestations with associated complications, and diagnostic studies were used. To establish a diagnosis, the treatment modalities provided and final outcomes were retrospectively reviewed and analyzed.Results: In all, 50 patients with a confirmed diagnosis of vascular tumors were enrolled. The median age at diagnosis was 11.5 years with equal gender distribution. The most common type of vascular tumor was hemangioma (n=41, 82%), followed by pyogenic granuloma (n=4, 8%), kapasiform hemangioendothelioma with Kasabach-Merritt phenomenon (n=2, 4%), infantile hepatic hemangioma (n=2, 4%), and juvenile nasal angiofibroma (n=1, 2%). The median age at diagnosis among patients with cutaneous vascular tumors (12.4 years) was significantly older than the age of those with visceral vascular tumors (1.3 years) witha P-value of 0.009. The mean size among patients with visceral tumors (7.46± 4.84 cm) was significantly greater than the size among patients with cutaneous tumors (3.21± 3.7 cm) with a P-value of 0.023. The size of the tumor was the only independent risk factor associated with clinical outcomes.Conclusion: Age at diagnosis in cutaneous vascular tumors was significantly older than in visceral vascular tumors. Clinical outcomes are favorable among most patients and the size of the tumors is an independent risk factor associated with outcomes.Keywords: pediatric, vascular tumor, prognostic factor, size, outcome